Analysis of short-term and local scale variations in fish community structure in Dachen Island waters - Cheng, Xiaopeng; Wang, Zhenhua; Zhang, Shouyu; Zhao, Xu; Lin, Jun; Huang, Hong; Chen, Yihui; Zou, Qindong (Frontiers in Marine Science, 2023)
Understanding the changes in community structure of fishery resources in island reef waters is crucial for effective fishery resource management, as these waters constitute a critical link in maintaining the sustainable development of offshore fishery resources. The study analyzed the structure of the fish community in the waters surrounding Dachen Island by using data collected during four voyage surveys conducted between September 2020 and April 2021. The study utilized co-occurrence network analysis, multiple regression trees, and functional diversity analysis to investigate the short-term and local scale changes in fish community structure. The results showed that the fish community in the waters adjacent to Dachen Island can be categorized into two groups: annual and stage-use species. The stage-use species include Scoliodon laticaudus, Trichiurus lepturus, Tetraodontidae, and others, which are used during the summer and autumn stages of bait migration. Additionally, Dasyatidae and others, which used during the winter and spring stages of reproductive migration. Furthermore, the study found that the habitats dominated by nearshore rocky habitats and distant deep habitats formed the local scale variation in community structure in island waters. The integrated analysis of species α-diversity and functional diversity provided a basis for understanding the mechanisms of biodiversity action. Our study aims to provide a theoretical framework for the development of fishery resource management strategies based on the life cycle of fish, and to serve as a reference for the prioritization of key protection areas for fishery resources in island and reef environments. Overall, the study’s findings can promote the understanding of community structure dynamics in island waters. Additionally, these findings can offer valuable insights into the restoration of habitats and the implementation of marine ranching activities in Dachen Island. Moreover, the outcomes can serve as a theoretical foundation for the development of appropriate management and conservation strategies for fisheries resources.